Plan de desarrollo 2008-2011 presentacion - Alcaldía de Medellín, Medellín es Solidaria y Competitiva (La Sociología en sus Escenarios, 2010)
Abstract. The Plan of Development 2008 - 2011 have the challenge to establish the continuity elements that require an action maintained and persistent in the time to obtain the transformation of Medellín within the framework of Integral the Human Development and to define the criteria that allow qualitative jumps that add value to him to the process of development in this period, especially concerning the social development, the fight against the poverty and the inclusion of the populations and the territories in situation of greater vulnerability. The continuity must avoid that the public management becomes inertial, that adopts the line of the smaller effort, without considering the profits, the advances, nor new realities in historical, political, economic and social, dynamic and changing contexts. The First draft of Plan of Development 2008 - 2011 look for to harmonize the following aspects: Emphasis in the social policy of the Program of Government Integrality with respect to the model of Integral Human Development Coherence with the Public Policies defined by the country and the city Joint with the local plans of development Effectiveness in the development and fulfillment of the missionary objectives Efficiency in the design, formulation and execution of the Projects The participation methodology was conceived from three approaches, the territorial one, sectorial and the population one. With first it was arrived at the settlers from the urban zones and at the groups of judges; with the second, it was summoned to social groups organized by population interests, such as: women, young people, population, disabled people, handicapped people, population LGBT, and displaced population; and with the third party, to organized social groups around sectorial interests: the commercial sector, the union sector, solidarity sector, the cultural sector and the sector of services. Resumen. El Plan de Desarrollo 2008 - 2011 tiene el reto de establecer los elementos de continuidad que requieren una acción sostenida y persistente en el tiempo para lograr la transformación de Medellín en el marco del Desarrollo Humano Integral y definir los criterios que permitan saltos cualitativos que le agreguen valor al proceso de desarrollo en este período, especialmente en lo que se refiere al desarrollo social, la lucha contra la pobreza y la inclusión de las poblaciones y los territorios en situación de mayor vulnerabilidad. La continuidad debe evitar que la gestión pública se vuelva inercial, que adopte la línea del menor esfuerzo, sin considerar los logros, los avances, ni nuevas realidades en contextos históricos, políticos, económicos y sociales, dinámicos y cambiantes. El Anteproyecto de Plan de Desarrollo 2008 - 2011 busca armonizar los siguientes aspectos: Énfasis en la política social del Programa de Gobierno Integralidad con respecto al modelo de Desarrollo Humano Integral Coherencia con las Políticas Públicas definidas por el país y la ciudad Articulación con los planes locales de desarrollo Eficacia en el desarrollo y cumplimiento de los objetivos misionales Eficiencia en el diseño, formulación y ejecución de los Proyectos La metodología de participación se concibió a partir de tres enfoques, el territorial, el sectorial y poblacional. Con el primero se llegó a los pobladores de las zonas urbanas y a los corregimientos; con el segundo, se convocó a grupos sociales organizados por intereses poblacionales, tales como: mujeres, jóvenes, población población en situación de discapacidad, población LGBT, y población desplazada; y con el tercero, a grupos sociales organizados alrededor de intereses sectoriales, como: el sector comercial, el sector sindical, el sector solidario, el sector cultural y el sector de servicios.